Unveiling Seniors’ Perception of Mobility: Urbanization, Region, and Physical Activity - Maresova P; Komarkova L; Horak J; Krejcar O; Kukuliac P; Vitkova L; Joukl M; Truhlarova Z; Tomsone S (Patient Preference and Adherence, 2023)
Petra Maresova,1 Lenka Komarkova,2 Jiri Horak,3 Ondrej Krejcar,1 Pavel Kukuliac,3 Lucie Vitkova,4 Miroslav Joukl,4 Zuzana Truhlarova,5 Signe Tomsone6 1Faculty of Informatics and Management, University of Hradec Kralove, Hradec Kralove, 500 03, Czech Republic; 2Faculty of Management, Prague University of Economics and Business, Jindrichuv Hradec, 37701, Czech Republic; 3Faculty of Mining and Geology, VSB—Technical University of Ostrava, Ostrava, 70800, Czech Republic; 4Philosophical Faculty, University of Hradec Kralove, Hradec Kralove, 500 03, Czech Republic; 5Faculty of Education, University of Hradec Kralove, Hradec Kralove, 500 03, Czech Republic; 6Faculty of Rehabilitation, Riga Stradins University, Riga, LV-1007, LatviaCorrespondence: Ondrej Krejcar, Faculty of Informatics and Management, University of Hradec Kralove, Rokitanskeho 62, Hradec Kralove, 500 03, Czech Republic, Tel +420737928745, Email ondrej.krejcar@uhk.czBackground: Maintaining mobility is fundamental to active aging, allowing older adults to lead dynamic and independent lives. The perception of mobility among older adults significantly impacts their overall well-being and quality of life. Given the aging population, mobility has become an increasingly pressing issue.Aim: This study focused on the perception of urban neighborhoods, including considerations of urban tissue (crossings and sidewalk maintenance), urban scenes (benches and traffic), and safety (fears and street lighting quality). We investigated the differences in the perception of the surroundings of residences by urban and rural seniors concerning their demographic and social characteristics and environmental determinants.Methods: A quantitative study design utilizing a questionnaire survey was employed. Data were collected mainly through face-to-face interviews in the field (PAPI) and via an online questionnaire (CAWI). The final sample comprised 525 participants. Hypotheses regarding the influence of gender, age, social status, level of physical activity, degree of urbanization, and region on environmental perception were tested using ordinal regression.Results: The hypothesis regarding the dependence of the perception of the surroundings on the level of urbanization was confirmed; that regarding the dependence of the perception of the residence surroundings on seniors’ age was not confirmed. The other hypotheses were partially confirmed. For the seven investigated environmental attributes, gender was significant in two cases, social status and physical activity in three cases, and region in four cases.Conclusion: While most studies have focused on urban settings, this study highlights the situation in rural municipalities. Substantially worse pedestrian conditions in availability of pedestrian crossings, benches, and lighting were recognized in rural municipalities versus cities. Understanding the complexity of mobility and the spatial locations relevant for older persons concerning potential barriers and facilitators for mobility aids in planning and adapting neighborhood environments to promote active and healthy aging in place.Keywords: seniors, mobility, walking, perception, survey